A review of health—related quality of life issues in children suffering from certain key otolaryngological illnesses - Chmielik, Lechosław Paweł; Mielnik–Niedzielska, Grażyna; Kasprzyk, Anna; Niedzielski, Artur (Frontiers in Pediatrics, 2023)
Background: The health – related quality of life (HRQL) concept is nowadays increasingly and more broadly used for helping evaluate the effectiveness of medical treatment, superseding the earlier “quality of life” approach. The HRQL concept likewise applies to otolaryngology and this narrative review study is focused on HRQL outcomes in four key childhood otolaryngological diseases as reported in the literature. Study aim: To retrospectively evaluate the literature on measuring HRQL in children suffering from selected otolaryngological illnesses, during treatment. Materials and Methods: Published studies/case reports were searched for in Medline, PubMed, Web of Science, Scopus and ORCID on the quality of life based on paediatric patient questionnaires, whether completed by subjects themselves or by their parents (by proxy). The following key words were used: health quality of life, otolaryngology/ENT, pediatrics/paediatrics. Studies before 1999 were omitted because hitherto, the "quality of life” had been imprecisely defined thus rendering any subsequent comparisions problematic. Results: HRQL scores and well-being were found to significantly deteriorate in child patients suffering from four important otolaryngological disorders: chronic sinusitis, nasal septum deviation, adenoid hypertrophy and hearing disease. The main problems found were infection, inflammation, disruption to family life and child-parental interaction, fitness-related issues, reduced ENT patencies and apnea. Conclusions: The HRQL appears to significantly deteriorate in children suffering from otolaryngological diseases. Further such studies are needed for other ENT diseases.